Associations of subjective vitality with DNA damage, cardiovascular risk factors and physical performance. (23rd April 2014) - Maynard, S.; Keijzers, G.; Hansen, Å.‐M.; Osler, M.; Molbo, D.; Bendix, L.; Møller, P.; Loft, S.; Moreno‐Villanueva, M.; Bürkle, A.; Hvitby, C. P.; Schurman, S. H.; et al.
Abstract Aim To examine associations of DNA damage, cardiovascular risk factors and physical performance with vitality, in middle‐aged men. We also sought to elucidate underlying factors of physical performance by comparing physical performance parameters to DNA damage parameters and cardiovascular risk factors. Methods We studied 2487 participants from the Metropolit cohort of 11 532 men born in 1953 in the Copenhagen Metropolitan area. The vitality level was estimated using the SF‐36 vitality scale. Cardiovascular risk factors were determined by body mass index (BMI), and haematological biochemistry tests obtained from non‐fasting participants. DNA damage parameters were measured in peripheral blood mononuclear cells (PBMCs) from as many participants as possible from a representative subset of 207 participants. Results Vitality was inversely associated with spontaneous DNA breaks (measured by comet assay) (P = 0.046) and BMI (P = 0.002), and positively associated with all of the physical performance parameters (all P < 0.001). Also, we found several associations between physical performance parameters and cardiovascular risk factors. In addition, the load of short telomeres was inversely associated with maximum jump force (P = 0.018), with lowered significance after exclusion of either arthritis sufferers (P = 0.035) or smokers (P = 0.031). Conclusion Here, we show that self‐reported vitality is associated with DNA breaks, BMI and objective (measured) physical performance in a cohort of middle‐aged men. Several other associations in this study verify clinical observations in medical practice. In addition, the load of short telomeres may be linked to peak performance in certain musculoskeletal activities.